A formação de pedagogos para o ensino de ciências nos anos iniciais - Silva, Vantielen da Silva (2014)
Science teaching presents many contribuitions for critical formation and reflexive formation of citizens. The access to scientific knowledges, through investigation, of experimentation and other ludic activities, represents a meaningful activity of students, since early years, may build knowledges which support the explanation about the world, the nature, the technologies and to themselves. Nevertheless, even that it is possible to understand the contribuition of the Natural Sciences, there are indicators that its teaching on the first stage in Basic Education need to be rethought, once teaching in this area, still worths the transmissions and knowledge memorization, not regarding the specificities and interests in childhood. Thus, it is recognized that reflecting about teaching occurs during the undergraduation of teachers of early years, in this situation, pedagogues act in different knowledge areas. Thinking about this, it is necessary to investigate the pedagogue s initial undergraduation to Science teaching in Paraná s State universities. More accurately, it was opted, through this investigation, to answer the question: What does it reveal about the initial formation of pedagogues about Science teaching in early years, in State universities in Paraná? It is clarified that this investigation is qualitative and for its development it is used different bibliographies and documents, which is emphasized the proposals of pegagogical policies of Pegagogy courses in Paraná State Universities and teaching plannings of subjects related to Science teaching. Also, we could count with interviews of undergraduated teachers from two State Universities. The use of these materials were given through the content analysis, from using Atlas t.i. software. In general, was identified the formation for Science teaching is lightned and fragile, the courses from State Universities in Paraná presents a subject whick talks about the area that it doesn t have an enough workload. Besides, the trainers professors have a little aproximation with the area and the studies are restrict to curricular issues to Science teaching during the early years. Thus, it is understandable that Pedagogy courses from Paraná must be rethought, worthing necessary specific areas to the performance during the early years and, also that must be rethought the selection of trainers professors who teach/undergraduate in Science areas.